Cholesterol lowering and inhibition of sterol absorption by Lactobacillus reuteri NCIMB 30242: a randomized controlled trial - Jones, M L; Martoni, C J; Prakash, S (European journal of clinical nutrition, 2012)
Background/Objectives: The percentage of hypercholesterolemic individuals not reaching their LDL-cholesterol (LDL-C) goal remains high and additional therapeutic strategies should be evaluated. The objective of this study was to evaluate the cholesterol-lowering efficacy and mechanism of action of bile salt hydrolase-active Lactobacillus reuteri NCIMB 30242 capsules in hypercholesterolemic adults. Subjects/Methods: A total of 127 subjects completed a randomized, double-blind, placebo-controlled, parallel-arm, multicenter study. Subjects were randomized to consume L. reuteri NCIMB 30242 capsules or placebo capsules over a 9-week intervention period. The primary outcome was LDL-C relative to placebo at the study end point. Results: L. reuteri NCIMB 30242 capsules reduced LDL-C by 11.64% ( P <0.001), total cholesterol by 9.14%, ( P <0.001), non-HDL-cholesterol (non-HDL-C) by 11.30% ( P <0.001) and apoB-100 by 8.41% ( P =0.002) relative to placebo. The ratios of LDL-C/HDL-cholesterol (HDL-C) and apoB-100/apoA-1 were reduced by 13.39% ( P =0.006) and 9.00% ( P =0.026), respectively, relative to placebo. Triglycerides and HDL-C were unchanged. High-sensitivity C-reactive protein and fibrinogen were reduced by 1.05 mg/l ( P =0.005) and 14.25% ( P =0.004) relative to placebo, respectively. Mean plasma deconjugated bile acids were increased by 1.00 nmol/l ( P =0.025) relative to placebo, whereas plasma campesterol, sitosterol and stigmasterol were decreased by 41.5%, 34.2% and 40.7%, respectively. Conclusions: The present results suggest that the deconjugation of intraluminal bile acids results in reduced absorption of non-cholesterol sterols and indicate that L. reuteri NCIMB 30242 capsules may be useful as an adjunctive therapy for treating hypercholesterolemia.